Crystal structures and photoluminescent properties of highly disordering lanthanide-2,5-pyridinedicarboxylate frameworks - Bunlawee Yotnoi (2020)
© 2019 Elsevier B.V. A series of [LnIII1.375(pydc)2(H2O)4] (Ln = SmIII (I), EuIII (II), GdIII (III), TbIII (IV), DyIII (V), HoIII (VI), ErIII (VII) and pydc2− = 2,5-pyridinedicarboxylate) were synthesized and characterized, disclosing a non-porous and highly disordering three-dimensional frameworks. The framework architecture is described based on four unique LnIII centers of two different square antiprismatic coordination spheres and discussed with reference to the closely relevant lanthanide coordination frameworks of pydc2−. Influences of the subtle change in synthesis parameters on crystallographic disordering and therefore diversity of the framework architectures are presented. The temperature-dependent photoluminescent properties of the titled complexes were studied, revealing variation in sensitization efficiency of pydc2− and the bi-exponential behavior in time-dependent luminescent decay. The influences of the crystallographic disorder in the framework structures on photoluminescent properties are demonstrated. Based on the temperature-dependent photoluminescent properties of the bimetallic [EuIIIxTbIII1.375−x(pydc)2(H2O)4] (VIII-X) and [SmIIIxTbIII1.375−x(pydc)2(H2O)4] (XI-XIII), the life times and the energy transfer efficiencies of the common TbIII-to-EuIII and the rare TbIII-to-SmIII energy transfer process have been studied. Temperature sensing performance of VIII-X and the potential of XIII as white light emitting material are also included.